Spontaneous rupture of the abdominal esophagus - González, Fernando; Sánchez, Fernando; Perrone, Luis (Cirugía del Uruguay, 1991)
Regarding a case of spontaneous rupture of abdominal oesophagus, authors analyse the following aspects: -severity of the clinical picture -pathogenesis linked to vomiting with intraoesophagic hypertension due to lack of re/axation of cricopharingea/ muse/e, anatoniopathological characteristics of the process, regional lesiona/ extension. -linic, where pain fol/owed by dyspnea, shock, cyanosis and abdominal defense stand out -diagnosis, based on clinica/ suspicion, radiology, fibroscopy and pleural puncture -surgical treatment with nutritional support and adequate antibioticotherapy.